2019
DOI: 10.1371/journal.pone.0217602
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of susceptibility to amikacin by 8-hydroxyquinoline analogs complexed to zinc

Abstract: Gram-negative pathogens resistant to amikacin and other aminoglycosides of clinical relevance usually harbor the 6’- N -acetyltransferase type Ib [AAC(6')-Ib], an enzyme that catalyzes inactivation of the antibiotic by acetylation using acetyl-CoA as donor substrate. Inhibition of the acetylating reaction could be a way to induce phenotypic conversion to susceptibility in these bacteria. We have previously observed that Zn 2+ acts as an inhibitor of the enzymatic a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 49 publications
(59 reference statements)
3
33
0
Order By: Relevance
“…In the case of the AAC(6 )-Ib, the most common aminoglycoside resistance enzyme among AAC(6 )-I-carrying Gram-negatives [21,32], some small molecules have been identified that act as enzymatic inhibitors [20,23,29,[33][34][35]. In addition to these advances, recent research revealed that Zn 2+ and other metal ions inhibit the acetylation of aminoglycosides mediated by AAC(6 )-Ib in vitro [25][26][27][28]36,37]. The mechanism by which these metal ions interfere with enzymatic acetylation of aminoglycosides mediated by AAC(6 )-Ib is not yet known.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of the AAC(6 )-Ib, the most common aminoglycoside resistance enzyme among AAC(6 )-I-carrying Gram-negatives [21,32], some small molecules have been identified that act as enzymatic inhibitors [20,23,29,[33][34][35]. In addition to these advances, recent research revealed that Zn 2+ and other metal ions inhibit the acetylation of aminoglycosides mediated by AAC(6 )-Ib in vitro [25][26][27][28]36,37]. The mechanism by which these metal ions interfere with enzymatic acetylation of aminoglycosides mediated by AAC(6 )-Ib is not yet known.…”
Section: Discussionmentioning
confidence: 99%
“…This path proved to be successful in the case of β-lactamase-mediated resistance to β-lactams [22,24]. The recent finding that metal ions such as Zn 2+ and Cu 2+ , in complex with ionophores, inhibit the acetylation of aminoglycosides mediated by AAC(6 )-Ib and reverse amikacin resistance in laboratory assays increased the expectations that viable formulations that can treat infections caused by resistant A. baumannii will be designed in the near future [25][26][27][28]. In this article, we describe the inhibition of AAC(6 )-Ib-mediated amikacin-resistance by Ag 1+ in A. baumannii and E. coli.…”
Section: Introductionmentioning
confidence: 99%
“…Barium has been described as a potent modulator with activation and blockage effects depending on cell and channel types (Inomoto and Tokimasa, 1998;Zhou et al, 2012;Wrighton et al, 2015;Kourghi et al, 2017), but its lack of selectivity precludes its use as a potential therapeutic drug. Recently, it has been shown that combination of antibiotics with zinc restore the susceptibility of antibiotic resistant Gram (-) bacteria (Magallon et al, 2019). This approach is worth of consideration, as the combination of anti-parasitic drugs of low efficacy with barium or other less toxic metals could increase the susceptibility of the parasites and provide new avenues for drug development.…”
Section: Discussionmentioning
confidence: 99%
“…Amikacin: Amikacin is an antibiotic of aminoglycoside class [ 55 ]. In our study amikacin showed interaction with Tyr495, tyr453, arg403, lys417 and glu406 residues of RBD region.…”
Section: Resultsmentioning
confidence: 99%